Comparison of Methods Used for Ultrasonic Examinations of IMT in the Wall of the Carotid Artery Model - TRAWIŃSKI, Zbigniew; WÓJCIK, Janusz (Archives of Acoustics, 2008)
The aim of this paper is to compare the results of examinations of the intima-media thickness(IMT) in the wall of the carotid artery model by means of zero-crossing and correlationmethods. The research was carried out on the elastic artery model (a pipe made of latex), withthe internal diameter of 3, 5 and 8 mm and the wall thickness of 0.75, 1.25 and 2 mm. A numericalsolver was created for the purpose of calculating the fields of ultrasonic beams andscattered fields under different boundary conditions, different angles and transversal displacementsof ultrasonic beams in respect of the position of the arterial wall. A VED ultrasonicapparatus was used during the investigations. The frequency of the transmitted ultrasoundwas 6.75 MHz. The numerical solver was used for the creation of ultrasonic RF reference signals.A good conformity was obtained between changing the numerical reference of the IMTand the results of determining the IMT by both the zero-crossing method and the correlationmethod.